The Social Significance of Mr. Nazeer Khan’s Architecture - Omer, Spahic (Journal of Islamic Architecture, 2015)
This paper discusses the social significance of Mr. Nazeer Khan’s architecture. The discussion revolves around the relationship between Mr. Nazeer Khan’s architecture and Kerala[1] Muslims’ economic transformation, as well as Kerala state’s inter-faith harmony. The study is not about delivering judgments concerning Mr. Nazeer Khan and his architectural exploits from a sheer perspective of architecture as a synthesis of art, science and technology, for such could significantly narrow at once our purpose and focus, and could divert our attention from some vital thrusts of the subject at hand. Rather, the study is about Mr. Nazeer Khan’s architecture and Kerala’s religious and socio-economic molds, and how they correlate with each other, the latter clearly dictating and shaping the former. It is only against this expansive and complex back-drop that Mr. Nazeer Khan’s architecture could be properly observed and appreciated. A restricted and one-sided approach – regardless of what it might be -- would in all likelihood lead to some incomplete, patchy and even unfair opinions and inferences. The paper is divided into six sections: (1) Introduction: why this study? (2) Who is Mr. Nazeer Khan? (3) Kerala Muslims’ economic transformation; (4) Mr. Nazeer Khan’s architecture and Kerala’s inter-faith harmony; (5) Mr. Nazeer Khan’s architecture: diversity in unity; (6) Conclusion. The content of this study is based, mainly, on the author’s lengthy interviews with Mr. Nazeer Khan and many of his clients, as well as on the author’s field visits to a majority of Mr. Nazeer Khan’s completed and on-going projects. The interviews and field visits took place in 2013 and 2014.[1] Kerala is a state in the south-west region of India.